Analisis Kelayakan Usaha Pada UMKM Ayam Geprek Sambal Lesung Paradisa - Ginting, Kristanto; Citra Indah Asmarawati (LPPM Universitas Putera Batam, 2024)
Business feasibility analysis in MSMEs Ayam Geprek Sambal Lesung Paradisa is an aspect of feasibility study assessment to avoid risks in a business. The purpose of this study is to assess the business feasibility of MSMEs Ayam Geprek Sambal Lesung Paradisa. To determine the level of feasibility in terms of several aspects, namely legal aspects, market and marketing aspects, technical and technological aspects, and management aspects. The research uses qualitative analysis from several aspects, namely legal aspects, market and marketing aspects, technical and technological aspects, and management aspects, the results of this study show that MSMEs Ayam Geprek Sambal Lesung Paradisa is feasible to run and have good prospects for development.